Towards Environmental Disclosure Based on Corporate Governance - Luluk Ifada (Indonesian Journal of Sustainability Accounting and Management, 2023)
This study examines the effect of Corporate Governance (CG) on Economic Performance (EP) and CG on environmental disclosure (ED). Besides, it examines the mediating role of Economic performance (EcP) on CG and ED; and Environmental performance (EnP) on EcP and ED. This research used secondary data from Bloomberg with a purposive sampling method to obtain 2084 Asian public companies from 2006 to 2020. This research used multiple linear regression methods for data analysis. The results showed that CG and EcP had an effect on ED. EcP could not mediate the relationship between CG and ED. Besides, there was no moderating role of EcP in the relationship between EcP and ED. This study suggests that CG and EcP are important for improving ED. Furthermore, stakeholders need to pay attention to CG, EcP, EnP, and ED regarding business assessment. This study provides empirical evidence about the mediating role of EnP in the relationship between EcP and ED in public companies in Asia Pacific. There was still little research that discusses the relationship between environmental, social, and governance issues of an organization and its financial profitability. As far as our search from previous studies, this is the first study that examines the effect of corporate environmental, social, and governance practices on financial performance in the context of developing countries.